The level of understanding on corporate image among university students: a case of Malaysian public university - Muhamad Husin, Nur Khairina; Romle, Abd Rahim; Pohyae, Saodia; Muhamad Husin, Zatun Najahah; Saberi, Nasarina; Abdullah, Muhammad Syafiq (ISLAMIC WORLD Network for Environmental Science and Technology (IWNEST Publisher), 2015)
The purpose of this paper is to analyze the level of understanding on corporate image among university students in Malaysian public university by using a cross-sectional personal-administered questionnaire.A total of 400 questionnaires were distributed for this purpose to the students from every level of their studies study in Universiti Utara Malaysia. Systematic random sampling procedure was used in selecting the sample for this study and data obtained was analyzed using the Statistical Package for Social Science (SPSS) version 21.0.Judging from the mean scores, the study suggested the overall score of the level of understanding about the corporate image in the university among the students were high importance.Finally, implications and some suggestions for this study have been provided and it can be very useful information for both academic and managerial purposes for the higher educational institution.